Law and neuroscience - Freeman, Michael D. A. (Oxford : Oxford University Press, 2011)
The latest volume in the 'Current Legal Issues' series offers an insight into the evolving state of law and neuroscience scholarship today. Focusing on the inter-connections between the two disciplines, it addresses the key issues informing current debates.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Medical laws and legislation; Neurosciences -- Law and legislation